PERAN KEPUASAN MEMEDIASI PENGARUH ATRIBUT PRODUK, DAN PENGETAHUAN TERHADAP KEPUTUSAN KONSUMEN - kamener, dahliana (Jurnal Benefita, 2016)
This study aimed to analyze the role of the Consumers Satisfaction in Mediating the Effect of Product Attributes and knowledge Of Products Embroidery Minang on consumers buying decisions. The population is consumers who decide to purchase the products in Padang. The spreading questionnaires to the consumers who have bought and used to wear the embroidery Minang. The  analysis was using descriptive, multiple regression analysis and statistical test tools by using Structural Equation Modelling SmartPLS 3. Finding indicated that the product attributes show positive not significantly effect on consumer decisions. Also knowledge indicate positive significantly influence on consumer decisions. Furthermore, Product attributes also tend to have a positive effect on satisfaction. Eventhough, Consumers knowledge have positive not significantly effect on consumers satisfaction and satisfaction has partially impact on consumers decisions. From this result it can be recommended that the industry of the Embroidery Minang should improve their attribute in term of design, style, color more unique that can be wear by all level of consumers and also the industries have to be more active in marketing and giving the knowledge of consumers.